Development of ultrathin thermal ground plane with multiscale micro/nanostructured wicks. (December 2020) - Yang, Yinchuang; Liao, Dong; Wang, Hongzhao; Qu, Jian; Li, Jian; Qiu, Huihe
Abstract: In this paper, TGPs with thickness of around 0.53–0.6 mm are developed with copper plate as the casing material, nanostructured copper foam as the wick and electroplated copper pillar as the support of vapor core. The effects of charge amount of water, nanostructured wick, the number of copper foam layers and vapor core thickness on the thermal performance of the developed TGP are experimentally studied. It is found that increasing the number of copper foam layers or vapor core thickness can greatly lower the TGP thermal resistance. Specifically, a TGP with a double layers copper foam wick has a much better thermal performance than that with single layer even though the total wick thickness and porosity remain unchanged. Experimental results also show that the multiscale micro/nanostructured wick is beneficial for improving the TGP thermal performance. Small change of vapor core thickness can lead to great change of TGP thermal performance. The ultrathin TGP can reach an effective thermal conductivity of 2207 W/(m·K) at an input power of 22.66 W over a heating area of 8 mm × 8 mm.